Research on DC-link Voltage Hold Control Strategy for EMUs Converter - Wei JIANG (机车电传动)
The characteristic and application of DC-link voltage hold mode for EMUs converter were introduced, and the DC-link voltage hold control strategy based on vector control was proposed. The influence of feed-forward compensation in control strategy was analyzed theoretically, and the calculation method of feed-forward power was provided. Finally, the validity of the control strategy was verified by the experiment results.